Instauration et coexistence de deux communautés de pratiques sur le Plateau de Millevaches (France): une contribution à l’étude des forêts comme terrains de vies - Eléonore Kirsch (Éditions en environnement VertigO, 2021)
In an industrialized context, based on a forest history marked by normativity, we propose to consider the instauration of forests and management practices as dynamic and territorialized negotiations. The practices of management actors and the forest resource, are shaped together by creating territories that are "land of life", rather than simple production means. In France, on the Plateau de Millevaches, two communities of forest managers compete for "good recipes" to promote either productivity or the biodiversity. First instaured as a hyper-productive socio-technical system, the monospecific forest serves economic revitalization. Mobilized by other actors as a place of ecological struggle, the actors of irregular forest becomes a platform for innovation, social cohesion and reflection on the consequences of industrialization. Between "techno-systematic" and "eco-systemic" management, differences in forest practices and definitions are sometimes a source of conflict. Each community is trying to build its forest management approach as an ideal. Yet these two dynamics, during their establishment processes, co-exist and influence in trajectories that are neither impervious to each other nor fenced. Reflecting together a complex forest and territorialized land of life, these two communities are considered here from the perspective of socio-ecology, in the service of a broader reflection on the transition and subsistence through inhabited, learning and plural forests.